A study of transient over-fuelling during heavy knock in an optical spark ignition engine - Vafamehr, Hassan; Cairns, Alasdair; Ebne-Abbasi, Hazhir (Inderscience, 2018)
The work was concerned with improving understanding of the effects of transient over-fuelling during heavy knocking combustion in modern spark ignition engines. The single cylinder engine employed included full bore overhead optical access capable of withstanding unusually high incylinder pressures. Heavy knock was deliberately induced under moderate loads using inlet air heating and a primary reference fuel blend of reduced octane rating. High-speed chemiluminescence imaging and simultaneous in-cylinder pressure data measurement were used to evaluate the combustion events. Under normal operation the engine was operated under port fuel injection with a stoichiometric air-fuel mixture. Multiple centred auto-ignition events were regularly observed, with knock intensities of up to ~30bar. Additional excess fuel was then introduced directly into the end-gas in short transient bursts. As the mass of excess fuel was progressively increased a trade-off was apparent, with knock intensity first increasing by up to 65% before lower unburned gas temperatures suppressed knock under extremely rich conditions. This trade-off is not usually observed during conventional low intensity knock suppression via over-fuelling and has been associated with the competing effects of reducing auto-ignition delay time and charge cooling/ratio of specific heats. Overall, the results demonstrate the risks in employing excess fuel to suppress knock deep within a heavy knocking combustion regime (potentially including a Super-Knock regime).